Natural Rubber Latex on Medical Applications - Barrera Torres, G; Rodriguez Urbina, JC; dos Santos, Renivaldo Jose; C Cabrera, Flavio; Sánchez G, Juan C; Jaramillo Carvalho, Jaime A (Journal of Community Medicine and Health Solutions, 2023)
In this review, latex from the Hevea Brasiliensis tree is presented as a material originating from nature, used to produce natural rubber, raw material for countless products for industry, as well as the manufacture of preservatives, and gloves, among others. Nowadays, its potential is expanding into various technological areas, one of which is biomedical, as described in this article. Latex has the possibility of being preserved using ammonium, which is a chemical of high health risk, but nowadays it is being substituted by acid systems excluding traditional chemicals. With these new preservation processes, the prospective use of latex for the design of biosensor scaffolds for drug release, and as membranes that can replace synthetic latex in patches for bioremediation in soft and bone tissues, synthetic muscles, membranes for biological micro laboratories, among others, is being studied to optimize its possibilities.